Scoping Review of the Use of High-Flow Nasal Cannulas in Covid-19 Patients - Alessa, Ahmad; Alanazi, Ali; Abudawood, Dalya; Filfilan, Nezar; Yamani, Ammar; Baeshen, Abdulrahman; Abdelrafea, Mohamed; Alnefai, Ameerah; Alharbi, Khalid (International Journal of Innovative Research in Medical Science, 2023)
This study aimed to explore the outcomes of using HFNC for patients with COVID-19. Forty-two studies were scanned using a scoping review, of which 22 were found eligible, satisfying the inclusion and inclusion criteria. Multiple patient outcomes were considered, including recovery time, oxygenation levels, reduced need for intubation in the future, ICU avoidance, and chances of respiratory distress. The findings suggest that HFNC remains more effective in treating patients with COVID-19-induced respiratory problems than traditional methods by indicating significantly improved oxygenation, reduced recovery time, reduced respiratory distress levels, and the need for invasive methods in the future. However, a few complications were also notable while considering its implementation on a wider scale, the most prominent being particle dispersion or airborne infection. However, the studies indicate that the complications and risks can be mitigated using precaution. The research seeks the validation of its findings through more comprehensive research in the future.